Expression levels of thymosin α1 in acute myocardial infarction patients and its correlation to cardiac function - Liu, Liang; Zhou, Zhen-Fa; Jin, Xian; Chen, Yu; Hu, Cui-Fen; Shen, Cheng-Xing (Frontiers in Cardiovascular Medicine, 2025)
BackgroundEarly prediction of heart failure (HF) after acute myocardial infarction (AMI) remains a clinical challenge. There is a lack of studies investigating Thymosin α1 expression levels in AMI patients and its relationship with cardiac function post-AMI.MethodsThis retrospective analysis included patients with AMI from December 2019 to February 2022. The baseline data of two groups were collected. Thymosin α1 expression level of peripheral blood plasma in AMI patients was examined by ELISA. Logistic regression analysis was applied to evaluate risk factors in-hospital cardiac dysfunction after emergency PCI in AMI patients. Receiver operating characteristic (ROC) curve was used to analyze the predictive value of the biomarker.ResultsA total of 307 hospitalized patients were enrolled in this study, divided into AMI group (n = 274) and non-AMI group (n = 33). The expression level of thymosin α1 in the AMI group was significantly higher than in the non-AMI group. The AMI patients were divided into two subgroups based on the EF values. The sample size was 64 (EF < 50%) and 210 (EF ≥ 50%), respectively. The expression of thymosin α1 in the EF ≥ 50% group was significantly higher than EF < 50% group. Spearman's correlation analysis demonstrated that thymosin α1 was positively correlated with the EF value. Logistic multivariate analysis suggested that thymosin α1, NT-proBNP, and creatine kinase were independent predictors of cardiac function after AMI. The AUC of thymosin α1, NT-proBNP, and creatine kinase was 0.614, 0.714, and 0.724, respectively.ConclusionThymosin α1 may serve as a potential biomarker to predict cardiac function following AMI. This study may provide novel insights into the potential therapeutic targets for HF following AMI.